Approach to amphibole in Zaydari Nasaviâs Nafthat-o-Almasdour - عطا محمد رادمنش; ندا پازاج (مطالعات زبانی و بلاغی)
“Nafthat-o-Almasdour” book is one of the excellent examples of technical and stilted prose in the seventh century. The author of this work with complete mastery and benefit from a variety of literal and spiritual figures of speech has revealed his art in the word processing. One of the literary arrays which Zaydri has benefited greatly from it is amphibole. The amphibole in this work is used more in the domain of a word rather than a sentence of a phrase and due to the significant proportion which is revealed between the words of the text, proportion amphibole considers as obvious industries in this secretary prose. In this paper, in addition of amphibole and proportion amphibole, paradox amphibole and immediacy amphibole and opacity of the conflict which are a subset of proportion amphibole are discussed. Total amphibole and syllepsis amphibole are cases which are discussed too.